Management of Unruptured Intracranial Aneurysms and Brain Arteriovenous Malformations. Issue 2 (April 2023) - Nguyen, Thanh Ngoc
ABSTRACT: OBJECTIVE: Managing a patient with an unruptured brain aneurysm or brain arteriovenous malformation (AVM) can lead to uncertainty about preventive treatment. While the bleeding risks are low, the morbidity or mortality associated with a hemorrhagic event is not insignificant. The objective of this article is to review the natural history of these vascular entities, the risk factors for hemorrhage, preventive treatment options, and the risks of treatment. LATEST DEVELOPMENTS: Randomized trials to inform preventive treatment strategies for unruptured intracranial aneurysms and brain AVMs are ongoing. Higher angiographic obliteration rates of unruptured intracranial aneurysms have been reported with the flow-diversion technique compared with alternative standard techniques. One randomized trial for unruptured brain AVMs showed a higher rate of morbidity and mortality in patients who underwent interventional treatment compared with observation. ESSENTIAL POINTS: The decision to treat a patient with a brain aneurysm should consider patient factors, the patient's life expectancy, aneurysm anatomical factors, and treatment risks. Patients with unruptured brain AVMs should be observed in light of recent clinical trial data or enrolled in an ongoing clinical trial.